Low power three phase inverter pure sinusoides output voltage design - Setiyono setiyono (Universitas Sarjanawiyata Tamansiswa, 2023)
The power conversion from direct current voltage (dc) to alternating current voltage (ac) is called an inverters generally produces a voltage or current waveform that has not approached the sinusoid or in other words, the wave still has ripple or distortion waveform with hight Total Harmonic Distortion (THD )value. One of the factors that influence the resulting inverter waveform is the inverter switchs triggering system. The PWM (Pulse Width Modulation) pulse generation method is a proposed way to solve this problem. To produce a three-phase voltage system, it takes 3 identical power converter circuits but has a different ignition system of 1200 phases for each inverter circuit. The simulation results show that the inverter with an input voltage of 24 V produces three voltage waves of 230/340 V with a Total Harmonic Distortion (THD) content value of 3.565%.